Cellular mechanisms of neuromodulation in a small neural network - Harris-Warrick, Ronald M. (Henry Stewart Talks, 2011)
Central pattern generators, Pyloric network in the stomatogastric ganglion, Neuromodulation of the pyloric network by dopamine, Ionic mechanisms of dopamine modulation, Synaptic mechanisms of dopamine modulation, Checks and balances in opposing actions of neuromodulation